STRUKTUR DAN FUNGSI SOSIAL CERITA RAKYAT LEGENDA SETEMPAT PINCURAN TUJUAH DI NAGARI KOTO TANGAH SIMALONGGANG DESA KAPALO KOTO KECAMATAN PAYAKUMBUH KABUPATEN LIMA PULUH KOTA - Sari, Yosi Novita; Zulfadhli, Zulfadhli (Universitas Negeri Padang, 2018)
This study aimed to describe: (1) the structure of folklore in local legend Pincuran Tujuah in Nagari Koto Tangah Simalonggang Village Kapalo Koto Kecamatan Payakumbuah Kabupaten Lima Puluh Kota, (2) social function of Folklore Legend Pincuran Tujuah. The type of research was qualitative research used descriptive method. Data were collected through interviews, observations, and recording of interviews with informants in Nagari Koto Tangah Simalonggang Kapalo Koto Village Payakumbuah Subdistrict, Lima Puluh Kota District. Based on the result of research, it is concluded the following things. First, Folklore Structure Legend Locally Pincuran Tujuah includes: (a) Characterization, consists of four characters, namely the main character and sideline. The main character is emak Gendong known as the person who has a patient and hard heart and while the side character is two children emak Gendong and neighbors who have a sense of jealousy to emak Gendong (b) Plot, the plot of legend Pincuran Tujuah is conventional groove, because a sequential event through regular causal relationships from the introduction of background, the main character, the entry into conflicts, and the ending of the story. (c) Background, this research is carried out in Nagari Koto Tangah Simalonggang Kapalo Koto Village Payakumbuah Subdistrict of Lima Puluh Kota Regency, and also there are also (d) Style of Language and (e) Less point of view is depicted in this legend story. Second, the social function of local folklore Pincuran Tujuah legend is as a function of educating, bequeath, identity, and tradition.Keywords: Folkore, Structure of Folklore, Social Function